Prostate Specific Antigen. Current clinical application and future prospects - Duskova, Katerina; Vesely, Stepan (Biomedical papers, 2015)
Background: Prostate-specific antigen (PSA) is a glycoprotein produced by the prostate gland and its production can be enhanced in benign and malignant diseases. The introduction of PSA testing has greatly increased the detection of prostate cancer. However there is continuing controversy and confusion over the most appropriate application of the PSA test.Methods: PubMed and Web of Science databases were used to search original and review articles on the historical aspects, clinical utilization and possible future directions in PSA.Conclusions: After its discovery, PSA was quickly established as an exquisitely sensitive tumor marker for prostate cancer detection, assessment of treatment responses and follow-up among patients with prostate cancer. Nevertheless, controversy exists about the proper threshold for recommending prostate biopsy. If this limit is lowered to improve the sensitivity even more, patients with low-risk prostate cancer would be subsequently detected. Post-treatment PSA levels can certainly provide valuable information about the effectiveness of the therapy given. Recently introduced ultrasensitive PSA detection techniques are offering new insight into the changes in serum PSA at very low concentrations. This has resulted in identification of valuable postoperative prognostic variables together with the possibility of earlier cancer relapse detection. The development of assays that may show superior sensitivity and specificity in prostate cancer diagnosis is focused on proteins possibly complexed with PSA and other potential markers detectable both in serum and urine. The goal of newly discovered prostate cancer biomarkers is greater cancer specificity in order to reduce the overdiagnosis, overtreatment and financial cost.
Keywords: PSA; prostate cancer; biomarkers